EVALUATION OF SOME FORMULATED DIETS FOR RE ING T POST-LARVAE OF MACROBRACHIUM ROSENBERGH - Indulkar, S. T.; Belsare, S. G. (Journal of Indian Fisheries Association, 2015)
Macrobrachium rosenbergii post-larvae with an average weight of 6.26 t0.23 mg and an average length of 10.67 t 0.13 mm were fed with one of the fiveexperimental diets having graded levels of lipid (5.0, 7.5, 10.0, 12.5 and 15.0%)to satiation two times a day to study their effect on growth, survival andfeed utilisation. The highest weight gain was observed in post-larvae fed7.5% lipid, although there was no significant difference (p > 0.05) betweengroups fed 7.5 and 10.0% lipid. Similar effect was observed in the specificgrowth rate and protein efficiency ratio of post-larvae fed the diet with 7.5and 10.0% lipid. The lowest feed conversion ratio was obtained in postlarvaefed the diet with 7.5% lipid. The survival rates of post-larvae fed onvarious levels of dietary lipid differed significantly (p < 0.05) after 15 days ofrearing period. Significantly lower survival was observed in the diet with15.0% lipid level. Dietary lipid did not significantly affect prawn carcassprotein, lipid and ash contents. Based on the data analysis (ANOVA - oneway analysis), the dietary lipid requirement for 15 days of nursery rearingof Macrobrachium rosenbergii post-larvae was estimated to be 7.5 to 10.0%under experimental conditions in this study.Keywords: Macrobrachium rosenbergii, post-larvae, nursery rearing,formulated diets, lipid requirement